(untitled) (Colección, 2017)
Latin America has experienced strong economic growth since 2003, in part benefited by an unusually very favorable external environment (such as high commodity prices) that may not continue in the medium-term. However, most of the countries in the region have continued practicing pro-cyclical fiscal policies even when in some cases such as Argentina a significant amount of the increase in revenues has been driven by the taxes on exports, achieved thanks to historically high export prices. The move towards counter-cyclical fiscal policies must start during good times in order to be credible for the market. The creation of a Stabilization Fund for revenues generated by taxes on exports in Argentina would be a politically viable measure towards a more responsible long-term fiscal policy.